Investigation of the effect of layer thickness and infill material percentage on the performance of low-cost and commercial fused deposition modelling / Muhammad Syamsuzzaman Shamsuddin - Muhammad Syamsuzzaman, Shamsuddin (2013)
Rapid prototyping (RP) technology is a new field in the manufacturing process. Unlike conservative manufacturing processes which are subtractive manufacturing process, RP applies an additive manufacturing approach. The layer-by-layer process mechanism of RP allows this technology to create complex geometry which is hard to achieve by traditional means. Fused deposition modelling (FDM) is one of the common processes in RP. In FDM, the raw material used is a spool of plastic filament, and polylactic acid (PLA) and acrylonitrile butadiene styrene (ABS) are the most common used materials. The plastic will be extruded through a heating element, then the plastic will be melted and will be extruded through a nozzle to create an exact shape of a part, in layer-by-layer means. In this project, layer thickness and infill material percentage are the parameters taken into consideration. The plastic injection molding specimen recorded 50.19363 MPa ultimate tensile stress, and used as a benchmark result. The commercial FDM recorded results in a range of 53.65% to 64.04% from the injection molding result, while the low-cost FDM was about 20.28% to 31.48%, depending on the case. Meanwhile for the compression test, the commercial FDM was obtained about 25.6 MPa to 46.17 MPa, depending on the case, while the low-cost FDM recorded in a range of 60.49% to 69.54% from the commercial FDM machine.